2021
DOI: 10.1002/er.7097
|View full text |Cite
|
Sign up to set email alerts
|

Highly improved solar cell efficiency of Mn‐doped amine groups‐functionalized magneticFe3O4@SiO2nanomaterial

Abstract: Herein, magnetic Fe 3 O 4 @SiO 2 nanomaterial functionalized with amine groups (Fe 3 O 4 @SiO 2 @IPA) doped with manganese (Mn) was prepared, characterized and used for solar cell application. Fe 3 O 4 @SiO 2 @IPA-Mn was prepared via the coprecipitation and sol-gel techniques. Energy-dispersive X-ray (EDX), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) measurements were performed to examine the structure of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…XRD patterns of the as-prepared Fe3O4, Fe3O4@SiO2, Fe3O4@SiO2@IIP, and Fe3O4@SiO2@NIP are shown in Figure 4. Compared with Fe3O4, Fe3O4@SiO2 showed the diffraction peaks of Fe3O4 at angles of 30.0°, 35.3°, 42.7°, 53.1°, 56.7°, and 62.3° corresponding to the (220), (311), (400), (422), (511), and (440) crystal planes of Fe3O4, respectively [24,25], which confirmed the successful compounding of Fe3O4 microspheres with SiO2. The XRD diffraction peaks of Fe3O4@SiO2@IIP and Fe3O4@SiO2@NIP were almost identical and became cluttered but, again, both retained the crystal plane of Fe3O4, verifying the successful introduction of Fe3O4 into the system of imprinted polymers.…”
Section: Xrdmentioning
confidence: 65%
“…XRD patterns of the as-prepared Fe3O4, Fe3O4@SiO2, Fe3O4@SiO2@IIP, and Fe3O4@SiO2@NIP are shown in Figure 4. Compared with Fe3O4, Fe3O4@SiO2 showed the diffraction peaks of Fe3O4 at angles of 30.0°, 35.3°, 42.7°, 53.1°, 56.7°, and 62.3° corresponding to the (220), (311), (400), (422), (511), and (440) crystal planes of Fe3O4, respectively [24,25], which confirmed the successful compounding of Fe3O4 microspheres with SiO2. The XRD diffraction peaks of Fe3O4@SiO2@IIP and Fe3O4@SiO2@NIP were almost identical and became cluttered but, again, both retained the crystal plane of Fe3O4, verifying the successful introduction of Fe3O4 into the system of imprinted polymers.…”
Section: Xrdmentioning
confidence: 65%
“…After modification with silane coupling reagent (curve 2), new peaks appeared at 1552 cm −1 , 1096 cm −1 , 869 cm −1 , and 469 cm −1 , which were assigned to the bending vibration of N–H, as well as the stretching vibrations of the Si–O–Si framework, Si–OH and Fe–O–Si, respectively. 22,23 In curve 3, the peaks at 2926 cm −1 to 2850 cm −1 and 1668 cm −1 were ascribed to the stretching vibrations of C–H from APTES and CO from secondary amine groups, respectively. In the NNK-MMIPs samples (curve 4), the characteristic peak at 1724 cm −1 was ascribed to the stretching vibration of CO groups in the crosslinking agent (EGDMA), which confirmed that the imprinted polymers are successfully synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…This peak indicates the presence of amine groups (-NH 2 ) on the surface of Fe 3 O 4 nanoparticles. Furthermore, the peak at 1582 cm −1 corresponds to the N-H bending mode of the amino group (-NH 2 ) that is attached to the surface of Fe 3 O 4 [25]. The weak board peak at 3059 cm −1 can be ascribed to the N-H stretching mode of an amino group (-NH 2 ) that is attached to the surface of Fe 3 O 4 [24].…”
Section: Structural and Morphological Analysismentioning
confidence: 99%